PENGURUSAN KUALITI MENYELURUH (TQM): SATU PERBANDINGAN ANTARA PRINSIP KONVENSIONAL DAN ISLAM - Abdul Ghani Azmi, Ilhaamie (Jurnal Syariah, 2019)
The article tries to differentiate the Conventional and Islamic principals that lies beneath Total Quality Management (TQM). Comparisons have been made on the definitions of quality, TM and its principals. It has been found out that Islam does not disregard any principals introduced by the Western as long as they do not transgress the Islamic principals. However, TQM in Islamic perspective is far away better than the conventional’s perspective as it aims not only for worldly sake but also for Hereafter which is known as al-falah.